Diagnostic Potential of Biosensors and Biomarkers in Pancreatic Cancer: A Comprehensive Review - Rani, Jyoti; Singh, Saravjeet; Kumar Sehrawat, Surender; Singh, Nitesh (Journal of Neonatal Surgery, 2025)
Pancreatic cancer (PC) being the primary cause of cancer-related fatalities across the globe is a hard and aggressive type of cancer that is typically diagnosed in the patients at the last phase. Currently, the average chance of surviving pancreatic cancer five years after detection is just 6 percent which highlights the need for early diagnosis and monitoring. Pancreatic cancer is traditionally diagnosed through imaging techniques such as CT scans, PET scans, magnetic resonance imaging, ultrasound, and biopsy. To get precise and understandable results, these methods are prolonged, expensive, and need the knowledge of experts in the field. Biosensors are emerging at a rapid pace that are used in the diagnosis of pancreatic cancer owing to their easy accessibility, cost-effectiveness accompanied with a high degree of precision. The present review investigated various biomarkers and biosensors along with their benefits and shortcomings which are extensively used in cancer detection. The study found that CA 19-9 biomarkers are best suited for diagnosis of pancreatic cancer due to its better performance and sensitivity. This review primarily helps biomedical engineers, doctors, and others researchers working in same domain in identification of potential research gaps and selection of most suitable biosensors for diagnosing pancreatic cancer